The Effect of Single Dielectric Barrier Discharge Actuators in Reducing Drag on an Ahmed Body - Saber Karimi; Arash Zargar; Mahmoud Mani; Arman Hemmati (Fluids, 2020)
The feasibility of a single dielectric barrier discharge (SDBD) actuator in controlling flow over an Ahmed body, representing a simplified car model, has been numerically and experimentally investigated at Reynolds numbers of <semantics>7.68×105</semantics> and <semantics>2.25×105</semantics>. The Ahmed body had slant angles of <semantics>25∘</semantics> and <semantics>35∘</semantics>. The results showed that SDBD actuators could significantly enhance the aerodynamic performance of the Ahmed body. Several arrangements of the actuators on the slant surface and the rear face of the model were examined to identify the most effective arrangement for drag reduction. This arrangement resulted in an approximately <semantics>6.1%</semantics> drag reduction. This improvement in aerodynamic performance is attributed to the alteration of three-dimensional wake structures due to the presence of SDBD, which coincides with surface pressure variations on the slant and rear faces of the Ahmed body.